Correlation between controlling nutritional status score and mortality risk in older Japanese adults diagnosed with dysphagia: a retrospective cohort study - Wang, Dong; Lv, Peng (Frontiers in Nutrition, 2026)
BackgroundThe Controlling Nutritional Status (CONUT) score has been established as a significant prognostic indicator of clinical outcomes in diverse, critically ill, patient populations. Nevertheless, limited research has explored the relationship between CONUT score and mortality risk among older Japanese adults diagnosed with dysphagia.ObjectiveTo evaluate the prognostic utility of the CONUT score in older Japanese adults diagnosed with dysphagia.MethodsThis single-center, retrospective, observational study included data from 235 older adults diagnosed with dysphagia to quantify the prevalence of malnutrition using the CONUT score and to delineate its independent prognostic relationship with mortality. The CONUT score was categorized as normal (0–1), mild (2–4), moderate (5–8), or severe (9–12) nutritional risk. Survival analysis was performed using Kaplan–Meier curves and time-stratified Cox regression analysis. Subgroup analysis was used to examine the consistency of the results.ResultsThis study included 94 male and 141 female patients, with a mean (±SD) age of 82.9 ± 9.3 years, of whom 85.96% were classified as having nutritional risk according to CONUT score. Kaplan–Meier curve analysis revealed a stepwise reduction in survival with worsening malnutrition, with median survival times of 936 days (normal), 468 days (mild), 266 days (moderate), and 52 days (severe). In time-stratified Cox regression analyses, higher CONUT scores were associated with increased mortality risk [continuous CONUT score: adjusted HR 1.11 (95% CI 1.03–1.19); p = 0.006]. After full multivariable adjustment, a significant dose–response relationship across ordinal CONUT categories was maintained (P for trend = 0.008). Compared with patients with normal nutritional status, those with severe malnutrition exhibited a higher point estimate of mortality risk [adjusted HR 2.61 (95% CI 0.97–6.96); p = 0.055], while mild and moderate malnutrition groups showed increased but statistically non-significant risks (p > 0.05).ConclusionThe CONUT score shows important prognostic value for mortality risk stratification in older Japanese adults with dysphagia. A significant dose–response relationship across malnutrition categories was observed, particularly when the score was analyzed as a continuous variable, highlighting its potential utility in clinical risk assessment. These findings suggest that routine CONUT screening may help identify patients at higher nutritional risk and support timely nutritional interventions in clinical practice.